KEMAMPUAN BAHASA PADA ANAK USIA 2-3 TAHUN MELALUI KEGIATAN CIRCLE TIME DI KB-TK LABSCHOOL JAKARTA - Serli Rahmayanti; Isti Rusdiyani; Kristiana Maryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language ability is one of the developmental aspects that needs to be stimulated from an early age because it plays an important role in children's communication, understanding of information, and interaction with their environment. Circle time is one of the learning activities that can be used to stimulate children's language ability. This study aims to describe the implementation of circle time, the development of receptive and expressive language ability of children aged 2-3 years, and the supporting and inhibiting factors in its implementation at KB-TK Labschool Jakarta. This research employed a qualitative approach with a case study design. The subjects consisted of the school principal, the classroom teacher, and 11 children aged 2-3 years. Data were collected through observation, interviews, and documentation, then analyzed through data condensation, data display, and conclusion drawing, with source and technique triangulation used to test data validity. The results show that circle time was implemented systematically through opening, core, and closing stages, and was able to stimulate children's receptive language in understanding simple instructions as well as expressive language in answering questions, enriching vocabulary, and forming simple sentences. The success of its implementation was supported by teacher competence, the use of appropriate media, activity routines, children's emotional readiness, and cooperation with parents, while the obstacles encountered included differences in children's language ability, short attention spans, children's emotional conditions, late arrivals, and the need for special assistance. Thus, circle time proved to be an effective learning strategy for stimulating the language ability of children aged 2-3 years.